2011
DOI: 10.15420/ahhj.2011.9.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Urine Albumin to Creatinine Ratio and Echocardiographic Left Ventricular Structure and Function in Patients with Essential Hypertension

Abstract: Background:Appearance of microalbuminuria, particularly in patients with hypertension, might be associated with a higher prevalence of left ventricular (LV) dysfunction and geometric abnormalities. This study was undertaken to determine whether high urine albumin to creatinine ratio (UACR) as a sensitive marker for microalbuminuria can be associated with LV hypertrophy (LVH) and systolic and diastolic LV dysfunction.Methods:The study population consisted of 125 consecutive patients with essential uncomplicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…12 Microvascular aging is common in hypertensive individuals, and people with micro-albuminuria showed higher prevalence of abnormal LV geometric patterns compared with those without micro-albuminuria. [13][14][15][16] A recent study showed that coronary artery atherosclerosis is associated with LV concentric geometry (LVCG), suggesting the greater cardiovascular risk associated with concentric remodeling and LVH. 17 A cohort study of 47,730 Koreans undergoing echocardiography revealed that mildly decreased estimated glomerular filtration rate (eGFR) had increased probability of LV geometry change represented by abnormal relative wall thickness (RWT).…”
Section: Introductionmentioning
confidence: 99%
“…12 Microvascular aging is common in hypertensive individuals, and people with micro-albuminuria showed higher prevalence of abnormal LV geometric patterns compared with those without micro-albuminuria. [13][14][15][16] A recent study showed that coronary artery atherosclerosis is associated with LV concentric geometry (LVCG), suggesting the greater cardiovascular risk associated with concentric remodeling and LVH. 17 A cohort study of 47,730 Koreans undergoing echocardiography revealed that mildly decreased estimated glomerular filtration rate (eGFR) had increased probability of LV geometry change represented by abnormal relative wall thickness (RWT).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table III, different cell sources were used: autologous or allogenic bone marrow MSCs from long bone 16,20,37,43,45,48,50–52 and iliac crest, 30,38,44,46,47 autologous adipose stem cells, 48,52 and location not specified. 15,49 The number of transplanted cells ranged from 1 to 30×10 6 .…”
Section: Resultsmentioning
confidence: 99%
“…15,49 The number of transplanted cells ranged from 1 to 30×10 6 . The cell injection timing included three different time points: in three studies, MSCs were injected during the distraction phase 15,37,49 or during the consolidation phase; 30,38,43,44,45,47,48,51 in three studies, the MSCs were injected on the day of the operation; 16,20,50 and in one study the time of injection was not stated 52 . The majority of the studies reported that MSC transplantation at the end of the lengthening phase with MSCs over 1 x 10 6 enhanced bone consolidation or formation in DO in animal models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation